Ambulance Cross-Border Operations Along the U.S.-Mexico Border: Current Practices in the El Paso-Ciudad Juarez Region. (June 2017) - Salgado, David; Aldrete, Rafael M.; Jolovic, Dusan; Martin, Peter T.; Rodriguez, Gustavo J.
Abstract : Background: Binational metropolitan regions consist of two or more different municipalities from two different countries connected by Ports-of-Entry (POEs). The El Paso-Ciudad Juarez binational metropolitan region has a population of approximately 2.5 million. Patients suffering from certain life-threatening conditions are frequently emergency-transported from Ciudad Juarez to a hospital in El Paso to receive specialized medical care. This research evaluated current ambulance cross-border operation protocols and practices followed in the El Paso-Ciudad Juarez region to transport these patients. Methods: This research was conducted in two stages. In the first stage, researchers conducted an extensive literature review to identify ambulance cross-border operation protocols currently in place worldwide. In the second phase, researchers used a series of meetings with agencies and organizations involved in the medical emergency transportation process in the El Paso-Ciudad Juarez region to characterize the problem and document the processes and protocols used by these agencies. The agencies included Mexican ambulance operators, U.S. Customs and Border Protection (CBP), and the El Paso Fire Department (EPFD). Results: Mexican ambulances transport patients to one of the POEs that connect Ciudad Juarez with El Paso. Once the Mexican ambulance arrives at the border, it has to wait in line with the rest of the passenger vehicles. As border officials realize an ambulance is approaching the border, they divert traffic so the ambulance can reach the CBP inspection booth as soon as possible. Then, officers quickly check the patient's documentation and call EPFD. The Mexican ambulance is then directed to a CBP secondary inspection facility so the patient is transferred to the EPFD ambulance. Finally, the patient is transported from the inspection facility to the hospital by the EPFD ambulance, and the Mexican ambulance returns to Mexico. The process involves multiple entities from both countries and one patient transfer. Conclusions: There is no formally agreed upon protocol to expedite ambulance cross-border operations between agencies and organizations on both sides of the border in the El Paso-Ciudad Juarez region. Each entity follows its own informal and independent operation protocol to the best of its ability. Therefore, the total transport time for patients that need to be emergency-transported from Ciudad Juarez to a hospital in El Paso to receive medical care can often exceed three hours. An improvement of the transportation time subsequently may impact the clinical outcome of these patients. The situation is similar in other binational metropolitan areas along the U.S.-Mexico border.